Navegación autónoma del Robot KUKA Youbot con señalización basada en técnicas de detección de objetos y redes neuronales profundas - Encalada, Patricio; Gordón, Carlos; Lema, Henry; León, Diego; Chicaiza, Dennis (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2019)
The processes of exploration and autonomous navigation implemented in ROS allow to generate routes depending on the space that the environment presents, however, it does not take decisions based on specific objects that are in the space since it does not incorporate by default a system of vision by computer that allows it to obtain data. Keywords: Deep Learning; autonomous navigation; detection objects; KUKA YouBot; Robot Operating System; Python. 1.Introducción Los robots móviles autónomos están causando un cambio de paradigma en la forma en que concebimos los vehículos comerciales en industriales. En el texto Autonomous robot navigation based on pattern recognition techniques and artificial neural networks, de Quiñonez et al. Hands-On Machine Learning with Scikit-Learn and TensorFlow: Concepts, Tools, and Techniques to Build Intelligent Systems (1 edition). Autonomous Robot Navigation Based on Pattern Recognition Techniques and Artificial Neural Networks.